2022
DOI: 10.56557/jogae/2022/v14i47703
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Growth and Yield Quality of Onion Plant via Foliar Application of Bio-Stimulants Under Different Nitrogen Sources

Abstract: There are environmental hazards of synthetic nitrogen fertilizers, however, there is a general tendency to raise the yield and quality of strategic crops in Egypt i.e., onion plant. Also, a little is known about the joint effects of different nitrogen sources as soil addition plus foliar spraying with bio-stimulants on onion plants. Thus, this research paper aims to assess the possibility of using compost as a partial substitute for synthetic nitrogen fertilizer with onion plants sprayed with some bio stimulan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Also, K plays a crucial role in regulating osmotic potential in pea plant cells, maintaining turgor pressure, and facilitating water movement within the plant. This can help plants cope with high-temperature stress and optimize their physiological functions (El-Sherpiny et al, 2022). On the other hand, it is involved in the activation of numerous enzymes, which are essential for metabolic processes.…”
Section: Resultsmentioning
confidence: 99%
“…Also, K plays a crucial role in regulating osmotic potential in pea plant cells, maintaining turgor pressure, and facilitating water movement within the plant. This can help plants cope with high-temperature stress and optimize their physiological functions (El-Sherpiny et al, 2022). On the other hand, it is involved in the activation of numerous enzymes, which are essential for metabolic processes.…”
Section: Resultsmentioning
confidence: 99%
“…Fulvic acids in potassium fulvate enhance the absorption of nutrients and improve plant resilience under stress conditions, including salinity. Potassium citrate also provided significant benefits, likely due to its role in osmotic adjustment and ion balance in plants under salinity stress (El-Sherpiny et al 2022;Soliman et al 2022;EL-Metwally et al 2023).…”
Section: Performance At a Period Of 70 Days From Sowingmentioning
confidence: 99%
“…Its application has been associated with increased chlorophyll content, better root development, and higher overall plant vigor. Potassium citrate, a water-soluble form of potassium, facilitates rapid absorption and utilization by plants, leading to improved physiological functions and stress tolerance (El-Sherpiny et al 2022;Soliman et al 2022;EL-Metwally et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed extracts are used to increase nutritional status, vegetative development, yield, and fruit quality in some plants. They contain a wide range of macronutrient and micronutrient nutrients as well as organic components such as growth hormones, amino acids, vitamins, betaines, cytokinins, and sterols (Abd El-Moniem and Abd-Allah, 2008;Khan et al, 2009;Spinelli et al, 2010 andEl-Sherpiny et al,2022). In general, Calvo et al (2014) in agriculture, reported that seaweed extracts can cause changes in physiological/biochemical processes related to nutrient intake and plant growth.…”
Section: Introductionmentioning
confidence: 99%